(untitled) (Heritage, 2021)
In all sciences, there is a general agreement that hypotheses can be defined under the rules of scientific defining. Consequently, with most authors in different sciences and scientific disciplines, it is indisputable that there is a general agreement of different theoretical and methodological directions that hypotheses are based on assumptions about the phenomenon, problem, and subject of research, which are expressed in the form of attitudes and judgments and have some cognitive value, in all sciences as well as in historical research. Hypotheses are determined by the definition of the problem, the subject of the research, and the goals of the research, primarily scientific ones. Hypotheses in all sciences, even historical ones, consist of variables and attitudes of a hypothesis that expresses the relations between variables. It is necessary to distinguish hypotheses in the process of acquiring scientific knowledge and in scientific research projects.